Women and power in Zimbabwe : promises of feminism - Shaw, Carolyn Martin, 1944- (UPCC book collections on Project MUSE. Global Cultural Studies., 2015)
The revolt against white rule in Rhodesia nurtured incipient local feminisms in women who imagined independence as a road to gender equity and economic justice. But the country's rebirth as Zimbabwe and Robert Mugabe's rise to power dashed these hopes. Using history, literature, participant observation, and interviews, Carolyn Martin Shaw surveys Zimbabwean feminisms from the colonial era to today. She examines how actions as seemingly disparate as an ability to bake scones during the revolution and achieving power within a marriage in fact represent complex sources of female empowerment.